2012
DOI: 10.1021/jp304444d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions of a Polyaromatic Surfactant C5Pe in Aqueous Solutions Studied by a Surface Forces Apparatus

Abstract: Studies on molecular mechanisms of polyaromatic surfactants in stabilizing water-in-oil (W/O) or oil-in-water (O/W) emulsions are of great scientific and practical importance. A polyaromatic surfactant N-(1-hexylheptyl)-N'-(5-carboxylicpentyl) perylene-3,4,9,10-tetracarboxylic bisimide (C5Pe) with well-defined molecular structure containing fused aromatic rings and heteroatoms similar to asphaltene molecules, was used in this study in an attempt to understand molecular interaction mechanisms of heavy oil compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
(90 reference statements)
2
34
0
Order By: Relevance
“…Because asphaltenes are enriched at the surfaces of oil phases (Natarajan et al 2011), such a system is highly relevant to the collection of crude oil onto a sorbent material. As would be expected based on double layer interactions, the forces between the surfaces coated with the model asphaltene molecule were greatly affected by changes in pH, monovalent salt concentration, and especially by Ca 2+ ion addition (Wang et al 2012). These results are generally in agreement with those by Svitova et al (2002), as mentioned in the earlier discussion of aqueous environmental properties.…”
Section: Electrostatic (Double Layer) Forcessupporting
confidence: 85%
See 1 more Smart Citation
“…Because asphaltenes are enriched at the surfaces of oil phases (Natarajan et al 2011), such a system is highly relevant to the collection of crude oil onto a sorbent material. As would be expected based on double layer interactions, the forces between the surfaces coated with the model asphaltene molecule were greatly affected by changes in pH, monovalent salt concentration, and especially by Ca 2+ ion addition (Wang et al 2012). These results are generally in agreement with those by Svitova et al (2002), as mentioned in the earlier discussion of aqueous environmental properties.…”
Section: Electrostatic (Double Layer) Forcessupporting
confidence: 85%
“…An electrostatic double-layer force arises when two surfaces come close enough for their diffuse layers overlap to an appreciable extent. Wang et al (2012) recently demonstrated the influence of the double layer in governing the forces between mineral (mica) surfaces in an aqueous system with the presence of a surfactant having characteristics similar to the asphaltene component of crude oils. Because asphaltenes are enriched at the surfaces of oil phases (Natarajan et al 2011), such a system is highly relevant to the collection of crude oil onto a sorbent material.…”
Section: Electrostatic (Double Layer) Forcesmentioning
confidence: 99%
“…Wang et al in Edmonton, Canada applied this technique to measure the interactions between mica surfaces covered with the model compound C5Pe both in organic solvent (toluene and heptane) 115 and aqueous phase 116 .…”
Section: Surface Forcesmentioning
confidence: 99%
“…To probe the role of charges on C5Pe model compound for the interfacial activity, Wang et al continued to measure the interactions between mica surfaces covered with the model compound C5Pe both in aqueous phases 116 . Repulsive forces were detected between two adsorbed C5Pe layers.…”
Section: Surface Forcesmentioning
confidence: 99%
“…Due to unknown molecular structures of asphaltenes that greatly hindered the progress on understanding the role of molecular forces in emulsion stabilization, surface forces were measured using asphaltene "model" compounds for a more nuanced understanding of surface forces at play. Using SFA recently for example, Wang et al 50 studied interaction forces for an asphaltene model compound known as C5Pe in aqueous solutions. C5Pe, also known as N-(1-hexylheptyl)-N′-(5-carboxylicpentyl) perylene-3,4,9,10-tetracarboxylic bisimide, consists of four aromatic rings fused together with three cyclic rings containing heteroatoms of O and N. 50 The interaction force (F/R) between C5Pe-coated surfaces was found to be repulsive, that is of steric and electrostatic origin.…”
Section: Oil/water/oilmentioning
confidence: 99%